2021
DOI: 10.1124/dmd.121.000681
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to High-Altitude Environment Is Associated with Drug Transporters Change: microRNA-873-5p-Mediated Alteration of Function and Expression Levels of Drug Transporters under Hypoxia

Abstract: Hypoxia is the main characteristic of a high-altitude environment, affecting drug metabolism. However, so far, the mechanism of miRNA involved in the regulation of drug metabolism and transporters under high-altitude hypoxia is still unclear. This study aims to investigate the functions and expression levels of multidrug resistance protein 1 (MDR1), multidrug resistance-associated protein 2 (MRP2), breast cancer resistance protein (BCRP), peptide transport 1 (PEPT1), and organic anion-transporting polypeptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…PXR is widely expressed in different areas of the brain, including BBB endothelial cells. ,, Otherwise, the expression of PXR has been approved to be potently inhibited under hypoxia . The in vitro experiment of Caco-2 cells also showed that the mRNA and protein expression levels of PXR were significantly decreased in various hypoxia concentrations and hypoxia time compared to the normoxia group . Are these above observations in our study relevant to PXR?…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…PXR is widely expressed in different areas of the brain, including BBB endothelial cells. ,, Otherwise, the expression of PXR has been approved to be potently inhibited under hypoxia . The in vitro experiment of Caco-2 cells also showed that the mRNA and protein expression levels of PXR were significantly decreased in various hypoxia concentrations and hypoxia time compared to the normoxia group . Are these above observations in our study relevant to PXR?…”
Section: Discussionsupporting
confidence: 50%
“…25 The in vitro experiment of Caco-2 cells also showed that the mRNA and protein expression levels of PXR were significantly decreased in various hypoxia concentrations and hypoxia time compared to the normoxia group. 54 Are these above observations in our study relevant to PXR? We observed that overexpression of PXR in rBMECs could significantly counteract the decrease of junction proteins and downregulate the increased p-IκB-α and p-NF-κB from OGD injury, but the difference was not significant between the two normoxia groups.…”
Section: ■ Resultsmentioning
confidence: 83%
“…In a previous study, we observed upregulation in the expression of 27 miRNAs and downregulation in the expression of 56 miRNAs in Caco-2 cells exposed to hypoxia. Further analysis confirmed that hypoxia led to a significant decrease in the expression of miRNA-873-5p; moreover, miRNA-873-5p possesses a similar effect as PXR on drug-metabolizing enzymes [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, downregulation of CYP3A1 and MDR1 expressions at both the protein and mRNA levels was observed. Moreover, according to our previous studies, the metabolism of midazolam and rhodamine 123, the corresponding substrates of CYP3A1 and MDR1 respectively, has changed accordingly ( Duan et al, 2022 ). In addition, CYP3A1 and MDR1 participate in the metabolism and transport of over half of currently used pharmacological agents ( Takano et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%